Business ownership experience, entrepreneurial behaviour and performance: novice, habitual, serial and portfolio entrepreneurs - Ucbasaran, Ayse Deniz (2004)
Recent media reports have drawn attention to entrepreneurs who have successfully owned several businesses. Entrepreneurs who have owned at least two businesses are known as 'habitual entrepreneurs'. However, not all habitual entrepreneurs are consistently successful. Further, studies show that habitual entrepreneurs are heterogeneous. A distinction has been made between portfolio entrepreneurs (i.e., those who own multiple businesses simultaneously) and serial entrepreneurs (i.e., those who have owned multiple businesses sequentially).